2017
DOI: 10.1177/0305735617692165
|View full text |Cite
|
Sign up to set email alerts
|

The expression of music throughout the lives of expectant parents

Abstract: Music can promote emotion regulation in individuals exposed to trauma and stress and may support positive parenting behaviors. The primary aim of the current study was to examine the use of music in the lives of a sample of expectant mothers and fathers (N = 102), who were considered at risk for insensitive parenting due to exposure to environmental and psychosocial stressors. Interviews probed childhood memories of music, current engagement with music, and parental plans to share music with their infants afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with prior research that has demonstrated that music interventions in group formats (Perkins et al, 2016; Shakespeare & Whieldon, 2018) and with lullaby focus (Carolan et al, 2012; Wolf, 2017a, 2017b) offer social and emotional benefits, such as enhancing parent–child connection (Mehr et al, 2016; Wulff et al, 2020) and parental mental wellness (Carolan et al, 2012; Dayton et al, 2017). This study extended this evidence base by investigating a novel remote administration of a music intervention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with prior research that has demonstrated that music interventions in group formats (Perkins et al, 2016; Shakespeare & Whieldon, 2018) and with lullaby focus (Carolan et al, 2012; Wolf, 2017a, 2017b) offer social and emotional benefits, such as enhancing parent–child connection (Mehr et al, 2016; Wulff et al, 2020) and parental mental wellness (Carolan et al, 2012; Dayton et al, 2017). This study extended this evidence base by investigating a novel remote administration of a music intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Thompson (2018) explored the impact of music therapy on families with young children on the autism spectrum, and qualitative results suggested a positive effect of music on the social relationship between the mother and the child. In another study, parents were interviewed about their use of music around their children, providing qualitative support for a positive impact of music on parent-child connection (Dayton et al, 2017).…”
Section: Music and Parent-child Connectionmentioning
confidence: 99%
“…Parents in this sample experienced relatively high rates of exposure to poverty and community and interpersonal violence and suffered from relatively high rates of symptoms of mental illness (e.g. depression, anxiety, post-traumatic stress disorder; see Dayton et al (2017) for a detailed description of violence exposure and psychiatric symptom rates for the sample).…”
Section: Study Samplementioning
confidence: 99%